REGULATING THE CRIMINAL PROCEDURAL STATUS OF OLDER PERSONS AS AN ELEMENT OF CRIMINAL POLICY:: NATIONAL AND INTERNATIONAL ASPECTS - V. Bertovskiy, Lev; M. Kurbatova, Svetlana (Revista Gênero e Interdisciplinaridade, 2021)
The relevance of the present study lies in the importance of observing human rights in all spheres, and especially in the field of criminal proceedings, taking into account its specifics and possible consequences for the persons involved. This is especially true for persons who, due to their cognitive capabilities, cannot always fully exercise their rights, and therefore cannot be full participants in criminal proceedings. Worldwide, the number of older persons is increasing, as does the likelihood of their involvement in criminal proceedings. At the international and national levels, the peculiarities of the legal status of minors are reflected in the legislation, yet no such rules of a compensatory nature exist for persons of old age. The current situation leads to the violation of their rights and necessitates the improvement of criminal policy both at the national and international levels, as well as the need for relevant scientific research. In this regard, the present research aims to identify or disclose the age characteristics of older persons in the context of the influence on the ability of these subjects to be full-fledged participants in criminal proceedings; to raise the issue of the need to reflect (in the content of criminal policy) the importance of legislative consolidation of the special legal status of these participants both at the national and international levels, including providing them with additional procedural guarantees (by analogy with the peculiarities of the participation of minors in criminal proceedings). Working on the issue, a cognitive approach was used, as well as general scientific and special, theoretical and empirical methods, which allowed comprehensively considering a number of aspects related to the research topic. The study presents the analysis of scientific literature and empirical research on the topic; a number of problems of national and international importance are identified concerning the legal situation (in the criminal process) of older persons; a number of proposals for improving the directions of the criminal policy of individual states and of the international community as a whole regarding the legislative consolidation of the peculiarities of the legal status of older participants is substantiated. The materials of the present research are of practical value for law enforcement agencies, for legislative, executive and judicial authorities, human rights organizations, and educational institutions